Ludo Game in Improving Dental Health Knowledge in Elementary School - Afifah, Nurul; Purnama, Tedi; Widiyastuti, Rini (Journal Center of Excellent : Health Assistive Technology, 2026)
Background: Dental and oral health problems remain common among elementary school children and may disrupt their daily activities and overall quality of life. One major contributing factor is the lack of knowledge about proper oral hygiene. Engaging and interactive educational methods, such as the Ludo game, can help improve students' understanding in a fun and enjoyable way. Objective: To analyze the effectiveness of dental health knowledge improvement before and after educational intervention using Ludo game media. Method: his study employed a pre-experimental with a one-group pretest-posttest design. A total of 32 students were selected as samples using a total sampling technique. Data were collected through questionnaires administered before and after the educational intervention, and analyzed using a paired t-test. Results: The average knowledge score before the intervention was 8,97 increasing to 13,91 after the intervention. The Paired t-test showed a p-value < 0.001, indicating a significant improvement. Conclusion: The Ludo game is effective in increasing dental health knowledge.